2017
DOI: 10.1093/pm/pnx160
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Empathy in the Patient-Doctor Relationship on Chronic Pain Relief and Quality of Life: A Prospective Study in Spanish Pain Clinics

Abstract: Physicians' empathy and patients' dispositional optimism have a role in determining positive outcomes in patients with chronic pain. Physicians' empathy may therefore be a suitable, yet relatively unexplored, target for intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 39 publications
1
24
0
1
Order By: Relevance
“…Del Canale et al 33 reported that physician empathy was associated with disease complications in diabetic patients. Cánovas et al 34 confirmed that doctors’ empathy helped to relieve pain in patients with moderate-to-severe chronic pain. These findings suggest that medical staff should focus on improving their empathy toward patients.…”
Section: Discussionmentioning
confidence: 95%
“…Del Canale et al 33 reported that physician empathy was associated with disease complications in diabetic patients. Cánovas et al 34 confirmed that doctors’ empathy helped to relieve pain in patients with moderate-to-severe chronic pain. These findings suggest that medical staff should focus on improving their empathy toward patients.…”
Section: Discussionmentioning
confidence: 95%
“…The positive effect of doctor-patient empathy on patients has been confirmed in previous studies. For example, Cánovas et al found empathy of physicians helped relief pain and increase quality of life in patients with chronic pain [38]. Thompson et al proved that empathy improved patient-centered care quality and the outcome of heart disease patients [39].…”
Section: Discussionmentioning
confidence: 99%
“…In healthcare, empathy is defined as a cognitive attribute involving an understanding of the patient's experience and perspective, as a separate individual, combined with an ability to communicate that understanding to the patient [ 16 ]. Interestingly, it has been suggested that high levels of empathy were related to positive outcomes for patients [ 17 – 19 ] and especially with chronic pain patients [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies support the benefits of PCC, [ 21 ]its use in chronic pain management seems to be challenging and suboptimal [ 20 , 22 ]. Patient-centered behaviour or communication does not necessarily translate into a “unique recipe,” and caregivers seem to use a flexible style according to patient characteristics [ 23 ].…”
Section: Introductionmentioning
confidence: 99%